Study of Cat Allergy Using Controlled Methodology—A Review of the Literature and a Call to Action - Hossenbaccus, Lubnaa; Linton, Sophia; Ramchandani, Rashi; Burrows, Alyssa G.; Ellis, Anne K. (Frontiers in Allergy, 2022)
The prevalence of cat allergen-induced AR is increasing worldwide, prompting its study using controlled methodology. Three general categories of allergen exposure models currently exist for the study of cat allergen-induced AR: natural exposure cat rooms, allergen exposure chambers (AEC), and nasal allergen challenges (NAC). We evaluated existing literature surrounding the use of these models to study cat allergen induced AR using online research databases, including OVID Medline, Embase, and Web of Science. We report that natural exposure cat rooms have been important in establishing the foundation for our understanding of cat allergen-induced AR. Major limitations, including variable allergen ranges and differing study designs highlight the need for a more standardized protocol. In comparison, AECs are an exceptional model to mimic real-world allergen exposure and study long-term implications of AR with large sample sizes. Existing AECs are limited by heterogenous facility designs, differing methods of cat allergen distribution, and issues surrounding cost and accessibility. Conversely, NACs allow for smaller participant cohorts for easier biological sampling and are ideal for phase I, phase 2 or proof-of-concept studies. NACs generally have a standardized protocol and are less expensive compared to AECs. Nevertheless, NACs solely capture acute allergen exposure and have the further limitation of using allergen extracts rather than natural allergen. As the use of combined controlled methodologies is sparse, we recommend concurrent use of AECs and NACs to study short- and long-term effects of AR, thereby providing a more holistic representation of cat allergen-induced AR.